2022
DOI: 10.1007/s11883-022-01033-7
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Cardiometabolic Health: Lessons Gleaned from the Pandemic and Insights for the Next Wave

Abstract: Purpose of ReviewTo review the current evidence regarding the impact of the coronavirus disease 2019 (COVID-19) pandemic on cardiometabolic health, with a focus on strategies to help mitigate adverse effects on population health. Recent Findings Individuals with cardiometabolic disease are particularly vulnerable to worse outcomes with COVID-19 infection. In addition, the pandemic itself has had significant deleterious impact on the cardiometabolic health of the population, including declines in physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…9 Increases in BP could be related to stress precipitated by the COVID-19 pandemic, increased sodium and alcohol intake, and decreased activity. 10 Another study demonstrated worsening SBP and DBP during the first 8 months of the COVID-19 pandemic among individuals with hypertension; however, once other solutions such as telemedicine were provided, BP began to stabilize. 11 These findings provide a possible explanation for the decrease in DBP found in our study from pre-SAH to post-SAH as telehealth was implemented.…”
Section: Discussionmentioning
confidence: 99%
“…9 Increases in BP could be related to stress precipitated by the COVID-19 pandemic, increased sodium and alcohol intake, and decreased activity. 10 Another study demonstrated worsening SBP and DBP during the first 8 months of the COVID-19 pandemic among individuals with hypertension; however, once other solutions such as telemedicine were provided, BP began to stabilize. 11 These findings provide a possible explanation for the decrease in DBP found in our study from pre-SAH to post-SAH as telehealth was implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies indicate that several cardiometabolic conditions are associated with increased risk for severe Coronavirus disease 2019 (COVID –19) 1 , 2 , 3 , especially obesity. 4 Given the strong association of obesity with severe COVID-19 and the close association of obesity with chronic kidney disease (CKD) both direct and indirect via obesity related cardiometabolic risk factors 5 , 6 , it is not surprising that CKD has been identified as the most prevalent severe COVID-19 risk factor worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] The intersection of COVID-19 with cardiovascular disease (CVD) was recognized early in the pandemic. Patients with CVD risk factors were identified as more likely to develop severe illness leading to hospitalization and death, [18][19][20][21] while CVD complications have been recognized as important contributors to the morbidity and mortality associated with COVID-19 infection. [22][23][24][25] Myocardial injury commonly occurs and is associated with more severe illness.…”
mentioning
confidence: 99%